169k views
2 votes
6x - 3 = 3( 2x - 1 ) what is the answer need it fast please and thank you

User Messerbill
by
5.6k points

2 Answers

2 votes

Answer:

x=x

Explanation:

6x-3=3(2x-1)

Used Distributive property to 3(2x-1)

6x-3=6x-3

Add 3 to both sides:

6x=6x

Divide 6 from both sides:

x=x

User Abanet
by
5.1k points
3 votes

Answer:

Any number for x will work

Explanation:

6x-3=3(2x-1)

expand

6x-3=6x-3

add three to both sides

6x=6x

simplify

x=x

Therefore any number for x will work

User Tumbudu
by
5.1k points